Investigating the reasons for storage of WEEE by residents – A potential for removal from households. (15th March 2019) - Nowakowski, Piotr
Highlights: Identified the reasons for storage of WEEE in households by residents. Mobile phones and IT equipment are commonly stockpiled as a spare. New behavioural WEEE disposal model is proposed. Proposals for improvement in removal of stockpiled waste equipment from households. Abstract: Some categories of waste electrical and electronic equipment (WEEE) escape legal methods of disposal. The waste stream intended for recycling is sometimes disrupted because of the stockpiling of end of life (EOL) equipment in households. In some cases this equipment may be non-functional or broken but it is kept by the individuals. It is usually equipment of small dimensions that is involved in these instances. The main purpose of this study is to identify the reasons that individuals stockpile EOL equipment. A behavioural model of WEEE disposal by household individuals is proposed and tested with a survey. Results from questionnaires show the differences in behaviour for individual categories of WEEE included in the survey conducted in Poland. The results show the significance of education, age, gender and type of residence on behavioural patterns relating to disposal of waste equipment. The most likely to be stockpiled are computer accessories and other information technology equipment, comprising above 60% of responses, and mobile phones, being above 80% of responses. The most frequent reason for stockpiling is intended possible use of the equipment in the future. The results of this research can be used in campaigns aimed at increasing household awareness against stockpiling.